The Impact of Sustainability Reports and Good Corporate Governance on Company Value Mediated by Financial Performance - Nurani, Susi; Kristianti Maharani, Novera (Journal Research of Social Science, Economics, and Management, 2025)
This study is designed to examine the impact of Sustainability Reporting and Good Corporate Governance (GCG) practices on firm value, with financial performance as a mediating variable, in primary consumer goods companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Firm value is measured using the Price to Book Value (PBV) ratio, while Sustainability Reporting is assessed through the Corporate Sustainability Reporting Index (CSRI) based on the GRI 2021 guidelines. GCG is represented by the proportion of independent commissioners, and financial performance is measured using Return on Assets (ROA). The sample consists of 29 companies, or 87 observations, selected through purposive sampling. Data analysis was conducted using multiple linear regression, path analysis, and the Sobel test. The findings reveal that both CSRI and GCG do not have a significant effect on PBV, whereas ROA shows a positive and significant effect on PBV. CSRI also has a significant negative effect on ROA, while GCG does not significantly influence ROA. The path analysis results indicate that the indirect effect of CSRI on PBV is smaller than its direct effect but remains significant in the Sobel test, suggesting partial mediation. In contrast, ROA does not mediate the relationship between GCG and PBV. Overall, these findings highlight that financial performance plays a more dominant role in determining firm value compared to Sustainability Reporting or GCG practices.